Reformulation of Restorative Justice Requirements in Handling Sexual Violence Based on Substantive Justice Values and Social Responsiveness - Abdul Jalil; Ruslina Dwi Wahyuni (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This study aims to reformulation the regulation of restorative justice requirements by considering social conditions grounded in substantive justice values. Restorative justice is an approach to resolving criminal cases that emphasizes the restoration of relationships among offenders, victims, and the community. However, in practice, the implementation of restorative justice tends to remain normative and formalistic and has not fully accommodated the dynamics of social conditions and justice values that exist within society, thereby potentially creating inequality in justice outcomes. This research employs a normative juridical approach combined with a socio-legal perspective. The data were obtained through a literature review of laws and regulations, legal doctrines, and relevant scholarly literature, and were strengthened by primary data collected through in-depth interviews with law enforcement officers and other stakeholders involved in the implementation of restorative justice. Data analysis was conducted using a descriptive-analytical method by examining the conformity between the normative regulation of restorative justice and social realities in society. The results indicate that the current regulation of restorative justice requirements remains focused on procedural and administrative aspects and has not optimally incorporated indicators of social conditions, local justice values, and community participation. Interview findings reveal a gap between regulatory frameworks and practical implementation, particularly in assessing the eligibility for applying restorative justice. Therefore, a reconstruction of the regulatory framework is necessary, emphasizing substantive justice values, flexibility toward social conditions, and active community involvement. This reconstruction is expected to realize a more contextual, humane, and socially just restorative justice system.